TREATMENT OF RESIDUAL WATERS OF THE TRADITIONAL AND ALTERNATIVE CURTIDE PROCESS THAT USES CHROME COMPANIES - Córdova Bravo, Hansel Miguel (2014)
Traditional methods of leather production in Peru consume on average between 60 to 80% of chromium for tanning process , generating wastewater with high concentrations of total chromium that must be treated in order to meet the Maximum Allowable Values ( VMA ) established by the DS 029-2009 - Vivienda. The use of complexing agents in the chrome tanning process reduces the supply of chromium to increase skin absorption. The main objective of this study was to evaluate the treatability by chemical precipitation of wastewater from traditional and alternative tanning process. It was determined that the optimal pH for the precipitation was between 7.36 and 9.99, the doses used besides sodium hydroxide were between 0.5 and 5.5 g / L, is the traditional process that requires higher dose . It was determined that the cost of the inputs used in the production of wet blue leather is more than the cost of inputs used in the treatment of wastewater from tanning when total chromium values are less than 650 mg / L.